Domestic medicine - Buchan, William, 1729-1805 (Salt Lake City, UT : Project Gutenberg, 2024)
"Domestic Medicine: or, a treatise on the prevention and cure of diseases" by William Buchan is a medical treatise written in the late 18th century. This publication serves as a guide to the general public, outlining methods for preventing and treating illnesses through lifestyle choices, diet, and simple medicines, as well as addressing nursing and managing children's health. The work emphasizes the importance of understanding health principles to navigate medical care effectively and minimize reliance on physicians in less accessible situations. The opening of the book establishes the author$1 (Bs commitment to improving medical knowledge among the public while highlighting the need for basic health education, particularly concerning the care of children and the influence of parents on their offspring$1 (Bs health. Buchan begins by discussing the impact of proper nursing and regimen on child mortality, reporting alarming statistics about infant deaths attributed to inadequate care and poor lifestyle choices. Additionally, he criticizes the common medical practices of his time, calling for a more intuitive and less secretive approach to healthcare that empowers individuals to take charge of their own well-being and that of their families. (This is an automatically generated summary.)s
Release date is 2024-09-03
Richard Tonsing and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Medicine, Popular -- Early works to 1800